A BIOAVAILABILITY STUDY OF INDONESIAN GENERIC TABLET OF CAPTOPRIL IN HEALTHY VOLUNTEERS - Nugroho, Agung Endro; Hakim, Arief Rahman; ., Purwantiningsih; Hakim, Lukman (Indonesian Journal of Pharmacy, 2012)
Captopril  is  a  selective  inhibitor  of  angiotensin-converting enzyme  (ACE)  and  is  formulated  by  several  pharmaceutical companies in Indonesia. This study was conducted to compare the bioavailability  of  a  captopril  tablet  with  reference  products  in healthy  volunteers.  The  relative  bioavailability  of  captopril  was determined in single dose, randomized, crossover,  and  two-phase studies.  The  relative  bioavailability  of  the  test  product  (a  generic captopril 50 mg tablet) with respect to the reference product was determined. Twelve healthy volunteers in two groups took part in these  studies  and  took  either  the  test  or  reference  tablets  in  the first  phase  and  received  the  other  tablet  in  the  second  phase  of each  study.  The  bioavailability  parameters  include  the  peak concentration  of  captopril  in  serum  (Cmax);  the  time  to  achieve the  peak  concentration  (Tmax);  and  the  area  under  the  curve  of captopril  in  serum  versus  time.  Non-compartmental  analysis  on observed concentration versus time data has resulted in the mean value of Cmax of 545.26 ± 22.90 ng/mL (test product) and 548.91 ± 25.07 ng/mL (reference product) and mean Tmax of 1.13 ± 0.08 hours  (test  product)  and  1.08  ± 0.08  hours  (reference  product), mean  of  AUC0-7  value  of  1820.51  ± 75.31  ng.  hour/mL  (test product)  and  1822.09  ± 99.29  ng.  hour/mL  (reference  product), and  mean  of  AUC0-inf  value  of 1967.83  ±  95.65  ng. hour/mL  (test product)  and  1996.94  ± 124.52  ng.  hour/mL  (reference  product). Based on the data, it can be concluded that there is no significant difference  (p>0.05)  in  bioavailability  between  both  captopril Tablet (test and reference product).Key words: Bioequivalence, Captopril, HPLC, Human serum, Generic